2015
DOI: 10.1021/acsmacrolett.5b00781
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Unsymmetrical Phenoxyiminato Dinickel Catalyst for High Molecular Weight Long-Chain Branched Polyethylenes

Abstract: An unsymmetrical bimetallic catalyst, (CF 3 / SO 2 )FI 2 -Ni 2 , having a CF 3 -functionalized phenoxyiminato Ni(II) center, which produces linear high-M w polyolefin (CF 3 /Ni) joined to an adjacent SO 2 -functionalized phenoxyiminato Ni(II) center, which produces highly branched low-M w polyolefin (SO 2 /Ni), was synthesized and fully characterized. In ethylene homopolymerizations, (CF 3 /SO 2 )FI 2 -Ni 2 affords monomodal (Đ = 1.7), highly, long-chain branched (69 branches/1000 C) polyethylenes with M w = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 55 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…A ligand‐asymmetric homobimetallic complex can offer the advantages of two active centers with different functions to synthesize PE with unique properties. Shu et al reported bimetallic complex 35 (Figure ), with unsymmetrical phenoxyiminato ligands inspired by a [Ti–Cr] heterobimetallic catalyst . However, the activity of complex 35 [20 kg PE (mol of Ni) –1 atm –1 h –1 ] is much lower than that of its mononuclear analogues [60, 335 kg PE (mol of Ni) –1 atm –1 h –1 ] under similar reaction conditions.…”
Section: Ni and Pd Catalysts And Their Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…A ligand‐asymmetric homobimetallic complex can offer the advantages of two active centers with different functions to synthesize PE with unique properties. Shu et al reported bimetallic complex 35 (Figure ), with unsymmetrical phenoxyiminato ligands inspired by a [Ti–Cr] heterobimetallic catalyst . However, the activity of complex 35 [20 kg PE (mol of Ni) –1 atm –1 h –1 ] is much lower than that of its mononuclear analogues [60, 335 kg PE (mol of Ni) –1 atm –1 h –1 ] under similar reaction conditions.…”
Section: Ni and Pd Catalysts And Their Effectsmentioning
confidence: 99%
“…Structures of catalysts 35 , 36 , 37a – c , 38a – d , 39a , 39b , 40a – d , and 41a – f , ,. [27b], , , …”
Section: Ni and Pd Catalysts And Their Effectsmentioning
confidence: 99%
See 3 more Smart Citations